Length of affected nerve segment in ulnar neuropathies at the elbow. (January 2022) - Podnar, Simon
Highlights: In ulnar neuropathy at the elbow (UNE) average length of the affected nerve segment was around 4 cm. Lengths of segments with reduced motor nerve conduction velocity and with increased nerve cross sectional area were similar. Affected segments were longer in right arms, arms with UNE due to entrapment, clinically more severe UNE and axonal UNE. Abstract: Objective: To establish length of the affected nerve segment (LANS) in ulnar neuropathy at the elbow (UNE). Methods: In a group of our previously reported UNE patients we identified 2-cm segments with reduced motor nerve conduction velocity (MNCV) on electrodiagnostic (EDx) studies and increased nerve cross-sectional areas (CSA) on ultrasonographic (US) studies. LANS was obtained by summation of these abnormal 2-cm segments separately for each approach. We also studied effect of selected independent parameters on LANS. Results: Altogether we studied 189 patients (194 arms). Mean (SD) LANS determined in 171 arms with reduced ulnar MNCV was 4.15 (1.89) cm, and was similar (p = 0. 21) to LANS obtained in 147 arms with increased CSA 4.46 (2.29) cm. Longer LANS were found in right arms, clinically severe UNE, axonal UNE and UNE due to entrapment. The most commonly affected 6 cm segment included 89% of abnormal 2-cm segments, with 50% of included 2-cm segments being normal. By contrast, the whole 10 cm segment included all abnormal 2-cm segments, with 66% of included segments being normal. Conclusions: In UNE both EDx and US studies revealed average LANS of around 4 cm. LANS was longer in more severe UNE. Significance: LANS needs to be taken into account in discussion of the mechanisms of UNE and approach to EDx diagnosis of UNE, particularly length of the segment used in nerve conduction studies across the elbow.